The role of apparent diffusion coefficient values in the differential diagnosis of breast lesions in diffusion-weighted MRI - (:unkn) unknown (AVES, 2013)
PURPOSE We aimed to determine the apparent diffusion coefficients (ADCs) of focal breast lesions on diffusion-weighted magnetic resonance imaging (DW-MRI) and to evaluate whether ADC measurement can be used to characterize lesions as benign or malignant. MATERIALS AND METHODS Fifty-one patients between the ages of 18-79 years (mean age, 48.5 years) with 51 histopathologically verified breast lesions were included in this study. The patients were examined with a 1.5 Tesla system using a bilateral phased-array breast coil. Spin-echo echo-planar imaging was used. The images were obtained with b values of 50, 400, and 800 s/mm(2). The ADC values were calculated for breast lesions and for normal fibroglandular tissue. Receiver operating characteristics analyses were performed to find the threshold ADC values. RESULTS The mean ADC was 1.42 +/- 0.17x10(-3) mm(2)/s for normal fibroglandular tissue, 1.9 +/- 0.45x10(-3) mm(2)/s for benign lesions, and 0.86 +/- 0.26x10(-3) mm(2)/s for malignant lesions. The threshold ADC value to differentiate bening and malignant lesions was 1.03x10(-3) mm(2)/s (sensitivity, 88.5%; specificity, 100%). With the ADC ratio (lesion to normal fibroglandular tissue), the threshold was 0.8 (sensitivity, 91.4%; specificity, 100%). The ADC value obtained from malignant lesions was statistically different from that of benign lesions (P<0.001). CONCLUSION Diffusion-weighted imaging can be used to differentiate malignant and benign breast lesions.
Keywords: PRINCIPLES; BENIGN